2017
DOI: 10.1038/s41598-017-01244-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of heterostructured WO3/TiO2 catalysts from wood fibers and its versatile photodegradation abilities

Abstract: A facile route was adopted to synthesize heterostructured WO3/TiO2 photocatalysts from wood fibers through a two-steps hydrothermal method and a calcination process. The prepared WO3/TiO2-wood fibers were used as photocatalysts under UV irradiation for photodegradation of rhodamine B, methylene blue and methyl orange. In calcination process, the wood fibers acted as carbon substrates to prepare the WO3/TiO2 photocatalysts with high surface area and unique morphology. Thus, the significant enhanced photodegrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 47 publications
1
39
0
1
Order By: Relevance
“…Figure 5 shows the N 2 adsorption-desorption isotherms of the pure TiO 2 and the PP-C-TiO 2 . It could be seen the curve for the PP-C-TiO 2 exhibits a hysteresis loop, which is attributed to type IV isotherms and the representative of mesoporous materials, indicating the presence of mesopores (2-50 nm) [17,18] , while the curve for the pure TiO 2 shows a type III isotherm, which indicates that the absorption property of the material is weak.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 5 shows the N 2 adsorption-desorption isotherms of the pure TiO 2 and the PP-C-TiO 2 . It could be seen the curve for the PP-C-TiO 2 exhibits a hysteresis loop, which is attributed to type IV isotherms and the representative of mesoporous materials, indicating the presence of mesopores (2-50 nm) [17,18] , while the curve for the pure TiO 2 shows a type III isotherm, which indicates that the absorption property of the material is weak.…”
Section: Resultsmentioning
confidence: 95%
“…1,2 Many investigations have been conducted to overcome these disadvantages and improve the photocatalytic performance, mainly including ion doping and the formation of heterojunction structures between two semiconductor materials. 5,8 Previous studies demonstrated that photocatalytic performance of semiconductor materials was signicantly enhanced due to the doping of non-metal elements N, 9 S, 5 and P, 10 or metal elements Cu, 11 Ag, 12 and Ce. 13 Liang et al proposed that Ag/TiO 2 and Ce/TiO 2 have high photocatalytic degradation performance for formaldehyde gas under UVlight.…”
Section: Introductionmentioning
confidence: 99%
“…13 The photocatalytic performance of catalyst can also be effectively improved by preparing a heterojunction structure between two semiconductor materials. 8 The formation of a heterojunction structure between two different semiconductors could broaden the spectral response range and reduce the recombination of photogenerated carriers. 14 Gao et al found that the photodegradation efficiency promoted for the WO 3 /TiO 2 heterojunction photocatalyst compared to WO 3 and TiO 2 under visible-light.…”
Section: Introductionmentioning
confidence: 99%
“…Los Ăłxidos metĂĄlicos como ZnO, TiO 2 , Cu 2 O, MnO 2 , Fe 2 O 3 , WO 3 y CeO 2 son compuestos formados por oxĂ­geno y un metal [1,2]. Dichos materiales pueden ser nanoestructurados y semiconductores, como el Ăłxido de tungsteno (WO 3 ) [3][4][5][6].…”
Section: Introductionunclassified